If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2t + -1) = 8 + -4t Reorder the terms: 4(-1 + 2t) = 8 + -4t (-1 * 4 + 2t * 4) = 8 + -4t (-4 + 8t) = 8 + -4t Solving -4 + 8t = 8 + -4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '4t' to each side of the equation. -4 + 8t + 4t = 8 + -4t + 4t Combine like terms: 8t + 4t = 12t -4 + 12t = 8 + -4t + 4t Combine like terms: -4t + 4t = 0 -4 + 12t = 8 + 0 -4 + 12t = 8 Add '4' to each side of the equation. -4 + 4 + 12t = 8 + 4 Combine like terms: -4 + 4 = 0 0 + 12t = 8 + 4 12t = 8 + 4 Combine like terms: 8 + 4 = 12 12t = 12 Divide each side by '12'. t = 1 Simplifying t = 1
| P(x)=x^3-2x^2-x-2 | | x/5-11=14 | | x/3-11=-14 | | (5/-9)+(7/6) | | 36=4a-16 | | 6xX-9=15 | | 4+17r-3=6r+40-2r | | 0.01(70)+x=0.06(70+x) | | -3y+8=4y+9 | | 25x-8=22x+16 | | 5.5q-2.8-4.6q=-0.1q-5.8 | | -2x+8x-4=20 | | 15(t-3)+6t=7(3t+2)-10 | | -3(4b+1)+(13b-9)=0 | | 1/3m-q | | 175*29/35*6/25 | | 9r=-45 | | m+2m=18 | | 9xX-28=15 | | (-2v)-7=-23 | | 3y+9/6y | | 3y-9/6y | | (n-5)*10=100 | | 4/17x=28 | | (n-5)*4=16 | | 140-5x=6x+9 | | 7(2b-3)+2=5*15+(b-3) | | y/3=13 | | -(7y+1)-(-6y-5)=0 | | 0=2x^2+4x-11 | | 3r+12r=30 | | 3(n-2)=22 |